Reading Comprehension Skill Using Graphic Organizer for Elementary School Students - Otang Kurniaman; Zufriady Zufriady; Eva Astuti Mulyani; Nugraheti Simulyasih SB (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
Reading comprehension is a substantial skill in elementary school. If childrenhave the skill to read, facing other lesson would be easy. This study employs aquantitative descriptive method that aims at explaining numbers in words. Theresult showed that the average of students' reading skill after being exposed tographic organizer-based reading comprehension teaching materials indetermining the basic thoughts was of 63.75, and students' skill in explaininginformation was 71.04. At this stage, their skill was considered good enough, sothat an improvement to design teaching materials and trainings should befacilitated for the teachers.